POTENTIAL PREY FOR JAVANESE LEOPARD (Panthera pardus melas Cuvier, 1809) AT THE MOUNT BOTOL RESORT, MOUNT HALIMUN SALAK NATIONAL PARK - Hasan, Silviana; Hasibuan, Ratna Sari; iskandar, sofian; Angguh, Teguh Angguh (Jurnal Nusa Sylva, 2025)
The Gunung Botol Resort is a conservation area in West Java that is crucial for the protection of key wildlife such as the Javan leopard (Panthera pardus melas Cuvier, 1809). The presence of the Javan leopard plays a crucial role in the ecosystem. Data on its potential is essential for efforts to maintain the sustainability of its population in the ecosystem. This study aims to determine the presence of Javan leopard prey at the Gunung Botol Resort in the TNGHS. This study was conducted using camera traps. Analysis of the obtained photographic data was carried out using the Jim Sanderson application. The results of the study produced 133 images, there were 8 types of Javan leopard prey animals that were successfully caught by Camera traps, namely forest rats (Rattus sp) 27 images, barking deer (Muntiacus muntjak) 25 images, wild boar (Sus scrofa) 19 images, linsang (Prionodon linsang) 17 images, jungle cats (Prionaliurus bengalensis) 16 images, squirrels (Tupaia javanica) 16 images, skunk teludu (Mydaus javanica) 10 images and Javan barking quail (Arborophila javanica) 3 images. These results indicate the availability of diverse natural food for Javan leopards as top predators functioning as umbrella species. This finding is important to support ecological-based conservation strategies, especially in maintaining the stability of top predator populations through sustainable habitat management and food chains.